Environmental And Thermal Performance Of Legumes As Biofacade In A Tropical Climate - Amir, Atikah Fukaihah (2013)
This is a thesis on a study of Biofacade, its carbon sequestration and its thermal reduction potential in urban environment. It is known that the rise of temperature through global warming is caused from excessive emission of carbon dioxide. Without denying urban development, Biofacades are alternative solutions. A Biofacade of leguminous climbing plant that serves as an agent to reduce the building wall surface temperature and overcome global warming by the storage of carbon dioxide in the plant tissue through carbon sequestration was studied in this research. There are three objectives in this research; to determine the suitable leguminous plant for use in Biofacade in tropical climate, to measure the carbon sequestration by leguminous plants in a Biofacade context for carbon trading prediction and to examine the thermal reduction by leguminous plants attached to the external walls. The plant studies and the carbon sequestration study were conducted for 14 months and over two cycles of planting. Four leguminous climbing plants were identified and the carbon sequestration rates of each were compared. The plant species of winged bean or Psophocarpus tetragonobulus has the second highest but the most stable sequestration rate and was chosen for the Building Thermal Performance experiment. With an experimental wall area of 9.175 m2, the Biofacade was stored as much as 0.935783 kg CO2-eq m-2 of Greenhouse gas emission annually. The study on the Building Thermal Performance was conducted for three days in Basic Study and for a month in Actual Building Scale.